Implications in occupational health for exposure to illumination and noise in workers in the footwear industry. - Morales Perrazo, Luis Alberto; Aldás Salazar, Darwin Santiago; Collantes Vaca, Santiago Marcos; Reyes Vásquez, Jhon Paúl (SATHIRI, 2019)
Disorders in the auditory and visual system of workers in the footwear industry depend on worker exposure to factors such as industrial noise and lighting conditions linked to their activities. This problem is analyzed throughout the evaluation of risks detected in these environments and their incidence in occupational health. The research includes the assessment of workstations of different manufacturing processes affected by the noise and luminance identifying the main sources of danger, estimating the risk, measuring noise and luminance levels and comparing these data with the permissible limits. Results indicated that 7% of the personnel exceed an exposure of 85 dB (A) which are categorized as a critical level that lead to an otological pathology. 44% of workers are exposed to insufficient illumination levels for the type of work they do and 54% are exposed to excessive illuminance. The workstations with the greatest exposure to the acoustic environment are cutting and finishing while to the light environment are sewing and assembling. The main effects of this phenomenon are visual fatigue, headaches, concentration problems and the increased of the auditory threshold.
Keywords: Noise; illumination; Otological Pathology; Visual Fatigue